Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien Di UPT Puskesmas XY - Herman Rupat; Reza Kurniawan Teuku (Sekolah Tinggi Ilmu Ekonomi Riau, 2025)
The study aims to determine the effect of service quality on patient satisfaction for outpatient care at the UPT Puskesmas XY. In this study, descriptive and quantitative analysis techniques were used to analyze the data. The sampling technique used was simple random sampling, with a sample of 100 people. Based on the research results, it can be concluded that simple linear regression discussion with the regression equation Y = 1.744 + 0.553X. The constant value of 1.744 means that if the independent variable X (Service Quality) is 0, then the dependent variable Y (Patient Satisfaction) is 1.744. The coefficient of regression value of variable X (Service Quality) is 0.553, meaning that if service quality increases by 1 unit, patient satisfaction will also increase by 0.553 units. The coefficient is positive, indicating a positive influence between service quality and patient satisfaction. The higher the service quality, the higher the patient satisfaction. The t-value for the independent variable Service Quality (X) is 14.520. The table can be seen in the statistical table at a significance level of 0.05/2 = 0.025 with degrees of freedom df = n - k or 100 - 2 = 98. The obtained t-table value is 1.98447 (t-table statistics). From these values, it can be concluded that t-value > t- table or 14.520 > 1.98447, which proves that Ha is accepted, and Ho is rejected, meaning that there is a significant effect of service quality on outpatient patient satisfaction at the UPT Puskesmas XY. The R² value is 0.683 or 68.3%. This value means that service quality contributes to patient satisfaction by 68.3%, while the remaining 31.7% is determined by other variables not present in this research model.